2018
DOI: 10.4103/picr.picr_81_17
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and comorbidity status in the treatment of type 2 diabetic patients attending a tertiary care hospital: An observational and questionnaire-based study

Abstract: Purpose/Aim:Diabetes mellitus is associated with several comorbid conditions. Thus, often, diabetic patients are prescribed multiple drugs. Although multiple drugs help to combat various diseases, they also increase the propensity of drug interactions and adverse drug reactions. The present study thus tried to evaluate the comorbid conditions and concurrent medications associated with type 2 diabetic patients. It also aimed to address patient compliance for the medications provided to them.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…In patients, it can adversely affect their adherence to medicines, quality of life and life expectancy, can lead to suboptimal blood glucose control and hospital admissions, and can increase severe hypoglycaemia risk and healthcare costs [10][11][12][13][14]. Studies conducted in different diabetes (including T2DM) populations and settings have reported a range of polypharmacy prevalence figures (6-85%) [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients, it can adversely affect their adherence to medicines, quality of life and life expectancy, can lead to suboptimal blood glucose control and hospital admissions, and can increase severe hypoglycaemia risk and healthcare costs [10][11][12][13][14]. Studies conducted in different diabetes (including T2DM) populations and settings have reported a range of polypharmacy prevalence figures (6-85%) [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…48% of patients with diabetes and hypertension in Canada were prescribed �9 medicines [19]. The average number of medicines prescribed to T2DM patients in India and Germany was five and 12, respectively [15,20]. A standardised universally accepted definition of polypharmacy is not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of additional medicine may also explain our results showing that the ORs of polypharmacy were associated with higher number of comorbidities, which is in line with recently published studies [ 15 , 21 , 43 45 ]. People with T2D are at high risk of arterial hypertension, cardiovascular disorder, hyperlipidemia, ect.,—all conditions, which require medicine: antihypertensive, antihyperlipidemic, antiplatelets medicines are often co-prescribed along with antidiabetic medicine [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPI-associated genes showed the maximum overlap (71%) with NIAD-associated genes followed by lipid-modifying/antiobesity drugs (38%), antihypertensives (25%) and antiarrhythmic/antiplatelet/anticoagulant agents (20%). This is highly relevant as the most coprescribed medications in Indian diabetes patients are hypolipidemics (72%), antihypertensives (68%), drugs for peptic ulcer (34.7%) and antiplatelets (10.7%) 35…”
Section: Resultsmentioning
confidence: 99%